Nancy Bermeo & Larry Μ. Bartels (επιμ.), Mass politics in tough times. Opinions, votes and protest in the great recession - Καφέ Αναστασία (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]